2017
DOI: 10.1177/0897190017735243
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing in Community Pharmacies: Keys to Success From Pennsylvania Pharmacists

Abstract: Successful POC testing services in community pharmacy practice rely on utilizing resources, partnering with known physicians, selecting meaningful tests for patients, and analyzing finances, workflow, and marketing to provide individualized attention and convenient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…Needs assessment can help pharmacies develop services that fit local communities and health systems by avoiding duplicative efforts that prompt competition. 17,26 Two studies examining community pharmacyebased GAS testing found that 43%-54% of the patients using the services did not have a primary care physician (PCP), and 38%-44% visited outside the traditional clinic hours. 9,27 Approximately one-third of the community pharmacies in Wisconsin are located in areas with known primary care shortages, as determined by an analysis of the DSPS list.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Needs assessment can help pharmacies develop services that fit local communities and health systems by avoiding duplicative efforts that prompt competition. 17,26 Two studies examining community pharmacyebased GAS testing found that 43%-54% of the patients using the services did not have a primary care physician (PCP), and 38%-44% visited outside the traditional clinic hours. 9,27 Approximately one-third of the community pharmacies in Wisconsin are located in areas with known primary care shortages, as determined by an analysis of the DSPS list.…”
Section: Discussionmentioning
confidence: 99%
“…This includes identifying the staffing, pharmacy technician role, time, workflow, space requirements, and patient privacy necessary for a successful POCT program and considering how the pharmacy could be restructured to meet these needs. 17,26 The managers spoke to the importance of this in the interviews, identifying a re-examination of schedules and workflow and a readjustment of physical space, technology, and equipment as key strategies for implementing POCT. Innovative practice models are being examined to help pharmacies grapple with the issue of how to address logistical constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 A CLIA-waived test is designed for screening, monitoring, or diagnosis outside of a laboratory setting and are used within a community pharmacy setting. 106 …”
Section: Community Pharmacy In the Usmentioning
confidence: 99%
“…Community pharmacists are also well-suited for health screenings to prevent disease and progression and help diagnose new diseases (i.e., type 2 diabetes). Community pharmacy-based point-of-care testing (POCT) such as blood glucose testing and rapid strep testing has shown to help manage chronic disease and acute illness with a good cost-to-benefit ratio, allowing for considerable cost savings for both public and government-funded medical systems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%